Stem cell membrane vesicle–coated nanoparticles for efficient tumor‐targeted therapy of orthotopic breast cancer. (17th January 2019) - Tian, Wen; Lu, Jianbo; Jiao, Dan
Abstract : Nanoparticles‐based drug delivery strategies have been widely researched for cancer therapy. However, most of them are expected to accumulate in tumor sites via the enhanced permeability and retention (EPR) effect, which is insufficient to deliver the loaded drug into tumors. Cell membrane–camouflaged nanoparticles have obtained much attention for their excellent stability and long blood circulation and reduced the macrophage cells uptake in drug delivery. Herein, bone marrow–derived mesenchymal stem cell membrane vesicle (SCV)–coated paclitaxel (PTX)–loaded poly (lactide‐co‐glycolide) (PLGA) nanoparticles (SCV/PLGA/PTX) were fabricated as the efficient orthotopic breast cancer–targeted drug delivery system. The SCV/PLGA/PTX showed excellent stability, more controlled PTX release, and more effective antitumor effect in vitro. After administration in vivo, SCV/PLGA/PTX exhibited the long‐term retention and enhanced accumulation at tumor sites due to the immune escape and mesenchymal stem cell–mimicking cancer‐targeting capacity. As expected, the SCV/PLGA/PTX could significantly suppress the primary tumor growth by increased apoptosis and necrosis areas within tumor tissues and attenuated the toxic side effects of PTX in 4T1 orthotopic breast cancer model. The study indicated the mesenchymal stem cell membrane coating strategy was highly efficient for targeted drug delivery, which provided a new insight for precise and effective breast cancer treatment.